The Therapeutic Principle of Combined Strengthening Qi and Eliminating Pathogens in Treating Middle-Advanced Primary Liver Cancer: A Systematic Review and Meta-Analysis - She, Yingqi; Huang, Qinfeng; Ye, Zhen; Hu, Yu; Wu, Mingquan; Qin, Kaihua; Wei, Ailing; Yang, Xin; Liu, Yuyao; Zhang, Cuihan; Ye, Qiaobo (Frontiers in Pharmacology, 2021)
Background: The combination of strengthening Qi and eliminating pathogens is an available therapeutic principle in traditional Chinese medicine for primary liver cancer at middle-advanced stage. However, there is lack of reasonable evidence to support the proper application of this therapeutic principle. This meta-analysis aims to evaluate the efficacy and safety of Chinese medicinal formulas, including two subgroup analyses of the principle of strengthening Qi and eliminating pathogens. Method: Clinical trials were obtained through searching of EMBASE, Web of Science, PubMed, Cochrane Library, Chinese National Knowledge Infrastructure, Wanfang Database, Chinese Scientific Journal Database, Chinese Biomedical Literature Database and two clinical trial registries. The randomized controlled trials with the combination of Chinese medicinal formulas and transcatheter arterial chemoembolization (TACE) in the experiment group were acceptable, in contrast to the TACE alone in the control group. The statistics analysis was performed on Review Manager 5.4. Results: A total of eligible 24 trials were accessed in this work. Overall, Chinese medicinal formulas could improve the survival duration of 6 months, 1 and 2-year, Karnofsky Performance Status, tumor objective response rate, AFP, and symptom. In the subgroup analysis, trials complying with the principle of single strengthening Qi did not show any significant difference in increasing tumor objective response rate. Meanwhile, the principle of combined strengthening Qi and eliminating pathogens was uncertain in improving symptoms, 1 year and 2-year survival time. In addition, the outcome indexes of ALT and AST was heterogeneous. In last, the total occurrence of adverse events could not be reduced via using Chinese medicinal formulas. Patients treated with Chinese medicinal formulas exhibited liver injury, fever, and white blood cell decline, with mild events occurring more frequent and severe events occurring less. Conclusion: Chinese medicinal formulas is an effective treatment method to cure primary liver cancer at middle-advanced stage. Adopting the principle of single strengthening Qi presents better efficacy in the long-term by prolonging the survival duration. Following the principle of combined strengthening Qi and eliminating pathogens could be more beneficial to patients in short term by lessening the tumor size. Chinese medicinal formulas has the advantage in reducing certain serious adverse events.